Creativity as a tool for understanding education: The role of creativity as a catalyst for educational transformation - Rodrigo-Martín, Isabel; Rodrigo-Martín, Luis; Pérez-García, Álvaro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The study proposes a theoretical framework for constructing a new perspective on Education based on the advances stemming from creativity research. In the first part of the research, we present a theoretical framework that allows us to rigorously approach the concept of creativity from an educational perspective. In the social framework, we look at the creative contexts needed in the teaching and learning process. We propose a model of educational context that responds to the needs of students. Finally, we propose the didactic framework, which addresses the new challenges and challenges of this education.